Analisis Relasi Teknologi, Institusi, dan Agensi dalam Transformasi Pelayanan Publik di Jakarta - Yani, Ely (Informasi, 2017)
This study focuses on the effort of public services through technology adoption. One offorms is the responsibility report Rukun Tetangga in Jakarta through the QlueapplicationThe implementation of Qlue is how it links between technology, institution, and agency.The author tries to review the process of relation among these three aspects occur topromote the transformation of public services in Jakarta through adoption of Qluetechnology for accountability report in RT. The main argument on this article is that theprocess of relation technology, institution, and agency as they become the main factorsin transformation of public services. This article attempts to give different perspectiveas the other articles with same themes only show the role of the advanced technology inpublic services. Via the depth interview and observation method in the place that becomethe sample is in one of the regions which using Qlue in its best way is KelurahanGalur,Central Jakarta. The conclusion, transformation through technology can occur whentechnology can be well institutionalized through rules. However, institutions mustalso be able to take into account the relationship between agents and the institutionalenvironment.AbstrakStudi ini berfokus pada upaya transformasi pelayanan publik melalui adopsi teknologi.Salah satu bentuknya adalah laporan pertanggung jawaban RT di Jakarta melaluiaplikasi Qlue. Implementasi Qlue merupakan kaitan antara teknologi, institusi danagensi. Penulis mencoba mengkaji mengenai bagaimana proses relasi antara teknologi,institusi, dan agensi dalam mendorong transformasi pelayanan publik di Jakartamelalui pengadopsian teknologi Qlue pada laporan pertanggung jawaban RT. Argumenutama dalam artikel ini adalah proses relasi antara teknologi, institusi dan agensimerupakan faktor yang sangat berperan dalam transformasi pelayanan publik. Artikelini mencoba mengisi pandangan dari artikel sebelumnya yang hanya memperlihatkanperanan perubahan teknologi dalam transformasi pelayanan publik. Melaluipendekatankualitatifdenganwawancara mendalam dan observasi di salah satu wilayahpenanganan Qlue terbaik yaitu kelurahan Galur, Jakarta Pusat. Kesimpulanartikelinitransformasi melalui teknologi dapat terjadi ketika teknologi dapat terinstitusionalisasidengan baik melalui aturan.Namun, institusi juga harus dapat memperhitungkanhubungan antara agen dan lingkungan institusional